Health: A Comprehensive Concept - Mordacci, Roberto (The Hastings Center report, 1998)
Health is one of those everyday words that only seems self-evident in its meaning. Physiological measurements alone fail to capture the subjective dimension of health. “Health” is an end and a means—it is a foundation for achievement, a first achievement itself, and a precondition for further achievement.